2015
DOI: 10.1089/scd.2015.0135
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Chondrogenesis and Enhanced Osteoclastogenesis in Leptin-Deficient Diabetic Mice (ob/ob) Impair Pathologic, Trauma-Induced Heterotopic Ossification

Abstract: Diabetic trauma patients exhibit delayed postsurgical wound, bony healing, and dysregulated bone development. However, the impact of diabetes on the pathologic development of ectopic bone or heterotopic ossification (HO) following trauma is unknown. In this study, we use leptin-deficient mice as a model for type 2 diabetes to understand how post-traumatic HO development may be affected by this disease process. Male leptin-deficient (ob/ob) or wild-type (C57BL/6 background) mice aged 6-8 weeks underwent 30% tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 24 publications
(37 reference statements)
1
9
0
Order By: Relevance
“…Up to now, no study has evaluated the expression of this transcription factor after extraction, relative to bone repair of fractures. Studies have demonstrated a delay in repair in diabetic animals, which is in agreement with the results obtained in the present study [ 33 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Up to now, no study has evaluated the expression of this transcription factor after extraction, relative to bone repair of fractures. Studies have demonstrated a delay in repair in diabetic animals, which is in agreement with the results obtained in the present study [ 33 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…CCN family members were first examined in a model of trauma-induced HO. Complete Achilles tenotomy, coupled with cutaneous dorsal burn injury, results in a well-characterized incidence of HO at the tenotomy site, replicating human disease (21)(22)(23)(24)(25). First, bulk RNA sequencing was performed at the tenotomy site and compared with the contralateral tendon site of the same animal (serving as an internal control) at 3 weeks after injury ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Leptin has differential effects on osteoclast number and activity in weight-bearing mice. ob/ob mice have normal or increased osteoclast-lined bone perimeter 25,26 , indicating that the hormone is not required for osteoclastogenesis. Indeed, subcutaneous administration of leptin attenuates ovariectomy- and HU-induced bone loss in rats by reducing osteoclast number 3,27 .…”
Section: Discussionmentioning
confidence: 99%